ANALISIS HUKUM DAGANG TERHADAP PRAKTIK KARTEL MINYAK GORENG KEMASAN DALAM PERSPEKTIF PERSAINGAN USAHA TIDAK SEHAT DI INDONESIA - I Gusti Ayu Widiadnyani (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2026)
This research examines the legal aspects of the packaged cooking oil cartel case from the perspective of unfair business competition in Indonesia. The scarcity and publicity of cooking oil prices from late 2021 to early 2022 caused public unrest and examined fairness in market competition. The Business Competition Supervisory Commission (KPPU) found allegations of coordinated product distribution by large producers. Using normative legal research methods, this study analyzes the application of Article 19 letter c of Law No. 5 of 1999 as implemented in KPPU Decision Number 15KPPU-I/2022. The results show that distribution creates artificial scarcity that is detrimental to consumers and small businesses, as well as causing market distortions and violations of fair trade principles. This study identifies obstacles to law enforcement due to complex legal exposure and procedures and recommends clear regulatory guidelines and stricter sanctions to improve the effectiveness of competition law enforcement and consumer protection in Indonesia.